Opinions and experiences of a national smokefree prison policy: evidence from the TIPs study. (30th September 2020) - Brown, A; Eadie, D; Purves, R; Demou, E; Mitchell, D; O'Donnell, R; Ford, A; Bauld, L; Sweeting, H; Hunt, K
Abstract: Background: Removal of tobacco from prisons poses distinct challenges, as prisons are 'homes' and smoking rates are high. TIPs is unique in comprehensively studying a smoking ban using data collected before, during and after the ban. This paper presents opinions and experiences of people in custody (PiC) and staff in Scotland, and identifies implementation success factors and lessons that are highly relevant for other jurisdictions and areas of public health. Methods: Surveys of staff and PiC (response rates) were conducted in Nov-Dec 2016 (27%, 34%), May-Jul 2018 (31%, 26%) and May-Jul 2019 (16%, 18%), with questions on smoking, smoking cessation/abstinence and smoking restrictions in the prison context. Topics were also explored qualitatively with staff/PiC at similar time points (34 focus groups, 99 interviews). Survey responses were analysed using descriptive statistics and logistic regression analyses. Qualitative data were thematically analysed to identify the diversity of views and experiences. Results: Smokefree policy is widely accepted as the new 'norm', but support was higher among staff than PiC before, during and after implementation. Surveys and qualitative data suggest perceptions of some of the potential difficulties (e.g. 'hard to enforce') and negative consequences (e.g. 'cause a lot of trouble') of smokefree policy reduced post implementation. Participants identified several implementation success factors relating to: planning and communication, smoking abstinence/cessation products/services, and partnership working. Conclusions: Smokefree prison polices can be successfully implemented, providing the removal of tobacco is well managed and support measures are available for smokers. Some factors shaping the successful introduction of smokefree prisons in Scotland are relevant to other areas of public health transformation e.g. setting clear objectives and timescales; collaboration and teamwork; and involving staff at all levels and end-users.